Preparation method for synthesizing polyglycolic acid with high intrinsic viscosity in ionic liquid

Polyglycolic acid was prepared by transesterification and solution polycondensation in ionic liquids, which solved the problems of chain exchange and depolymerization caused by high-temperature melt polycondensation. This method enabled the synthesis of polyglycolic acid with high intrinsic viscosity, high molecular weight, and high mechanical strength.

CN119264388AInactive Publication Date: 2025-01-07BEIJING UNIV OF CHEM TECH
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411584018.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-01-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the existing technology for preparing polyglycolic acid, high-temperature melt polycondensation easily leads to side reactions such as chain exchange and depolymerization, resulting in low molecular weight and wide distribution, and requiring multiple reactors and high-pressure equipment.

Method used

Polyglycolic acid prepolymers were prepared by transesterification at room temperature using ionic liquids as solvents, followed by solution polycondensation in the ionic liquids. Catalysts such as lanthanum oxide and antimony oxide were used to control the reaction temperature and pressure to avoid local overheating at high temperatures.

Benefits of technology

The synthesis of high intrinsic viscosity polyglycolic acid was achieved, avoiding chain exchange and depolymerization side reactions, improving monomer conversion and product yield, and reducing energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264388A_ABST
    Figure CN119264388A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of polyglycolic acid. According to the method, firstly, methyl glycolate is subjected to transesterification to prepare a polyglycolic acid oligomer, then the oligomer forms oligomer powder under the action of mechanical crushing, and finally, the powder is subjected to post-polycondensation in ionic liquid based on bis (trifluoromethanesulfonic acid) imine to obtain a polyglycolic acid product. The invention also provides a preparation method of the ionic liquid based on the bis (trifluoromethanesulfonimide), which comprises the following steps: firstly, carrying out quaternization reaction on N-methylimidazole and 1-halogenated alkane to generate the ionic liquid based on bromine anions; and then the ionic liquid intermediate and lithium bis (trifluoromethanesulfonyl) imide are subjected to an ion exchange reaction to prepare the ionic liquid based on the bis (trifluoromethanesulfonyl) imide. The invention provides a preparation method of polyglycolic acid, which has the advantages of simple post-treatment and reusability of post-treated ionic liquid, and the prepared polyglycolic acid has high intrinsic viscosity and is expected to be used in human body surgical sutures.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of biomedical applications, and in particular relates to the synthesis of an ionic liquid having good solubility for polyglycolic acid and a preparation method for synthesizing polyglycolic acid by solution polycondensation in the ionic liquid. Background Art

[0002] Plastics have the advantages of light weight, high strength, excellent plasticity, low production cost, good chemical resistance, low thermal conductivity and good electrical insulation. Therefore, they are widely used in human life, such as food packaging, construction, medical and transportation. However, as people have a better understanding of plastics, they find that common materials such as polyethylene, polypropylene, polystyrene and polyvinyl chloride are non-degradable materials. Such non-degradable materials take dozens or even hundreds of years to degrade, causing serious land waste and land pollution. In this case, people began to study degradable plastics, that is, plastics that can be degraded into substances that are not harmful to the natural environment (such as carbon dioxide and water) under natural conditions. Polyglycolic acid, one of the degradable plastics, has become one of the most studied and applied degradable plastics in recent decades because it has the least carbon number per unit (produces less carbon emissions during degradation), fast degradation rate (completely decomposes into water and carbon dioxide within 30 days), excellent biocompatibility, extremely high gas barrier properties and high mechanical strength. Nowadays, common polyglycolic acid preparation methods include glycolic acid direct polycondensation method, glycolide ring-opening polymerization method and glycolic acid methyl ester direct polycondensation method. Compared with the other two polymerization methods, the polycondensation of methyl glycolate has the advantages of a short synthesis route and the byproduct methanol is easy to remove compared to water. Nowadays, the preparation of polyglycolic acid by melt polycondensation of methyl glycolate is to remove small molecule methanol under high temperature and high vacuum conditions to obtain high molecular weight polyglycolic acid. However, due to the high temperature, this method is prone to side reactions such as polyglycolic acid hydrolysis and chain exchange between macromolecular chains, resulting in low molecular weight and wide molecular weight distribution of polyglycolic acid. Ionic liquid is an organic salt that exists completely in liquid form at 100°C. It has the characteristics of almost no vapor pressure, non-flammability, excellent chemical stability and thermal stability, and good biocompatibility. In addition, ionic liquids can have different solubility parameters by designing different cations and anions, and have been widely used as solvents to synthesize polymers (polyamide, polyimide and polyester, etc.). Therefore, the preparation of polyglycolic acid with high intrinsic viscosity by ionic liquids is a feasible and worthy research direction.

[0003] CN112010834A uses methyl glycolate as a monomer, tin molecular sieve as a ring-forming catalyst, and tin catalyst as a ring-opening polymerization catalyst to prepare polyglycolic acid by first forming a ring and then opening the ring. The catalyst used in this method can be recycled, the conversion rate of methyl glycolate reaches 99%, and the weight average molecular weight of the synthesized polyglycolic acid is greater than 100,000. However, this method requires a high-pressure reactor as a container.

[0004] CN111763308A first H3PW 12 O 40 Mixed with SnO2 to prepare a composite catalyst, methyl glycolate is then used to generate a polyglycolic acid prepolymer at 160-180°C, 70-100Pa and the catalytic action of the composite catalyst, and then the temperature is raised to 200-240°C for polymerization to obtain polyglycolic acid. In this method, the heteropoly acid is used as a catalyst for both polymerization and end-capping. However, in this method, polyglycolic acid is prepared by melt polycondensation, and the temperature in the late stage of polymerization reaches 240°C, at which time the polyglycolic acid has undergone thermal decomposition reaction.

[0005] In CN111647142A, the synthesis of polyglycolic acid is divided into three processes, namely prepolymerization, intermediate polymerization and postpolymerization. As the reaction proceeds, the polymerization pressure gradually decreases and the polymerization temperature gradually increases, which is conducive to the removal of by-products to synthesize high molecular weight polyglycolic acid. However, this method requires multiple reactors, and melt polycondensation easily leads to a wide molecular weight distribution. Summary of the invention

[0006] In order to solve the problems existing in the prior art, the present invention provides a method for preparing polyglycolic acid with high intrinsic viscosity in an ionic liquid. The present invention first uses methyl glycolate to prepare polyglycolic acid oligomers through an ester exchange reaction, and then the oligomers are polycondensed in an ionic liquid to prepare polyglycolic acid. The advantage of preparing polyglycolic acid in an ionic liquid is that it is conducive to heat exchange to avoid local overheating. At the same time, compared with preparing polyglycolic acid by melt polycondensation, solution polycondensation can prevent the occurrence of side reactions such as chain exchange and depolymerization of polyglycolic acid under high temperature conditions.

[0007] In order to achieve the technical purpose of the present invention, the technical solution adopted by the present invention is as follows:

[0008] The present invention provides a method for preparing polyglycolic acid with high intrinsic viscosity in an ionic liquid, comprising the following steps:

[0009] The polyglycolic acid prepolymer, the ionic liquid and the polycondensation catalyst are subjected to polycondensation reaction to obtain polyglycolic acid with high intrinsic viscosity.

[0010] The polyglycolic acid with high intrinsic viscosity provided by the present invention can have the ratio of raw materials adjusted according to actual needs during the preparation process, such as the mass ratio of the polyglycolic acid prepolymer to the ionic liquid is 1:1-2, preferably 1:2.

[0011] The polycondensation catalyst is selected from one or more of lanthanum oxide, antimony trioxide, tin oxide, cerium oxide, antimony acetate and zinc acetate.

[0012] Optionally, the amount of the polycondensation catalyst added is 0.1-1 wt %, preferably 0.1-0.5 wt %, of the total amount of the reactants (polyglycolic acid prepolymer and ionic liquid).

[0013] In the preparation process of polyglycolic acid with high intrinsic viscosity provided by the present invention, the specific reaction parameters of each reaction can be adjusted according to the amount of raw materials used and actual needs. For example, the polycondensation reaction temperature is 150-240°C, the pressure is 0-2000Pa, and the time is 8-16h, preferably 12-16h.

[0014] Specifically, the method for preparing polyglycolic acid with high intrinsic viscosity can be defined as follows, comprising the following steps:

[0015] Add polyglycolic acid prepolymer and ionic liquid in a mass ratio of 1:1-2 into a dry reactor, stir them evenly, add 0.1-0.5wt% of the total amount of reactants into a polycondensation catalyst, carry out a solution polycondensation reaction for 12-16h at a vacuum degree of 0-2000Pa and a temperature of 150-240°C, and then stop the reaction to obtain polyglycolic acid with high intrinsic viscosity.

[0016] Optionally, the method for preparing the polyglycolic acid prepolymer comprises the following steps:

[0017] Under normal pressure, methyl glycolate undergoes an ester exchange reaction (temperature and normal pressure) under the catalysis of an ester exchange catalyst, and then evacuates and maintains a constant temperature, and continues to react under negative pressure to obtain a polyglycolic acid prepolymer.

[0018] The transesterification catalyst is selected from NaOH, Na2CO3, K2CO3, AlCl3, ZnCl2, SnCl2, H3PW 12 O 40 One or more of .

[0019] The added amount of the transesterification catalyst is 1% of the mass of methyl glycolate.

[0020] The temperature of the transesterification reaction under elevated temperature and normal pressure is 100-150°C and the time is 5-7h.

[0021] Under negative pressure, the pressure is 0.5-5kPa and the time is 2-3h.

[0022] Specifically, the preparation method of the ionic liquid comprises the following steps:

[0023] A) adding N-methylimidazole and 1-halogenated alkane to toluene to carry out quaternization reaction to obtain the corresponding imidazole type halogen salt;

[0024] B) dissolving the imidazole type halide salt in water, and adding bistrifluoromethanesulfonyl imide lithium to carry out ion exchange reaction to obtain an imidazole type ionic liquid with bistrifluoromethanesulfonyl imide as anion.

[0025] The dosage ratio of the N-methylimidazole, 1-halogenated alkane and toluene is 1 mol:1 mol:100 mL.

[0026] The molar ratio of the imidazole type halide salt to lithium bis(trifluoromethanesulfonyl)imide is 1:1.05.

[0027] Optionally, the quaternization reaction temperature is 30-60° C. and the reaction time is 24-48 h.

[0028] Optionally, the ion exchange reaction temperature is 30-60° C. and the reaction time is 6-12 h.

[0029] The ionic liquid system based on bistrifluoromethanesulfonyl imide provided by the present invention has good solubility for polyglycolic acid, is conducive to reaction under high vacuum, thereby improving the reactivity of low-activity functional groups, and can remove small molecular byproducts at a lower temperature. The present invention introduces common transesterification catalysts and polycondensation catalysts, and the resulting polyglycolic acid has a high intrinsic viscosity.

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] 1. Compared with the preparation of polyglycolic acid under high temperature and high vacuum by melt polycondensation, the preparation method provided by this patent prepares polyglycolic acid by solution polycondensation, which is conducive to heat exchange to prevent local overheating and side reactions such as depolymerization and chain exchange. The preparation method provided by the present invention prepares polyglycolic acid by solution polycondensation using ionic liquid. The synthesized polyglycolic acid has a high intrinsic viscosity, that is, the synthesized polyglycolic acid has a high molecular weight, which means that the synthesized polyglycolic acid has a high mechanical strength and is expected to be used in artificial bones.

[0032] 2. The present invention selects direct polycondensation of methyl glycolate rather than direct polymerization of glycolic acid and ring-opening polymerization of glycolide, which has the advantages of short synthesis route, easier removal of by-product methanol compared to water, low energy consumption and high product yield.

[0033] 3. The present invention first synthesizes polyglycolic acid prepolymer by ester exchange reaction of methyl glycolate, and then synthesizes polyglycolic acid by polycondensation reaction of the polyglycolic acid prepolymer. This preparation method can improve the conversion rate of monomers and reduce the residual amount of monomers that do not participate in the reaction. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Characterization and analysis: Fourier transform infrared spectroscopy (FT-IR) and Raman spectroscopy were used to characterize the chemical composition of the ionic liquids in detail.

[0035] Thermal properties test: Differential scanning calorimetry (DSC) was used to characterize the melting point of the synthesized polyglycolic acid.

[0036] Figure 1 The synthetic route of ionic liquids and polyglycolic acid based on bis(trifluoromethanesulfonyl)imide anions.

[0037] Figure 2 The infrared spectrum of the ionic liquid based on the bistrifluoromethanesulfonyl imide anion is shown at 640 cm -1 、3060cm -1 The peaks are -SO2- and CH on the benzene ring, indicating that the ionic liquid based on the bistrifluoromethanesulfonyl imide anion was successfully synthesized.

[0038] Figure 3 The Raman spectrum of the ionic liquid based on the bis(trifluoromethanesulfonyl)imide anion is 1230 cm -1 It is the characteristic peak of -CF3, which further indicates that the ionic liquid based on bistrifluoromethanesulfonyl imide anion was successfully synthesized.

[0039] Figure 4 The DSC graphs of polyglycolic acid synthesized based on different ionic liquids show that the polyglycolic acid synthesized by 1-ethyl-3-methylimidazolium bis-trifluoromethanesulfonyl imide salt ionic liquid has the highest melting point. At the same time, as the alkyl chain on the imidazole increases, the melting point of the polyglycolic acid synthesized based on its ionic liquid decreases. Among them, the melting point of the polyglycolic acid synthesized by 1-benzyl-3-methylimidazolium bis-trifluoromethanesulfonyl imide salt ionic liquid is between 1-ethyl-3-methylimidazolium bis-trifluoromethanesulfonyl imide salt and 1-propyl-3-methylimidazolium bis-trifluoromethanesulfonyl imide salt.

[0040] Figure 5 The characteristic viscosity of polyglycolic acid synthesized based on different ionic liquids is the highest for polyglycolic acid synthesized based on 1-ethyl-3-methylimidazolium bis trifluoromethanesulfonyl imide salt ionic liquid. At the same time, as the alkyl chain on imidazole increases, the characteristic viscosity of polyglycolic acid synthesized based on its ionic liquid decreases. Among them, the characteristic viscosity of polyglycolic acid synthesized by 1-benzyl-3-methylimidazolium bis trifluoromethanesulfonyl imide salt ionic liquid is between 1-ethyl-3-methylimidazolium bis trifluoromethanesulfonyl imide salt and 1-propyl-3-methylimidazolium bis trifluoromethanesulfonyl imide salt. DETAILED DESCRIPTION

[0041] In order to better understand this patent, the following will explain this patent through examples and appendices. It should be noted that the following patent is only a further explanation of this patent, and professionals in related fields can make further adjustments based on the content of this patent.

[0042] Embodiment 1:

[0043] (1) Methyl glycolate is placed in a reactor, and SnCl2 with a mass% of methyl glycolate is added. The mixture is first heated to 100°C at normal pressure and stirred for 1 hour, and then the temperature is increased by 10°C every hour until the temperature reaches 150°C and maintained at this temperature for 3 hours. The reaction is then continued for 3 hours under a vacuum of about 5 kPa to obtain a polyglycolic acid prepolymer.

[0044] (2) Preparation of 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide ionic liquid:

[0045] N-methylimidazole, ethyl bromide and toluene were added into a dry reactor in the ratio of 1 mol:1 mol:100 mL, heated and stirred at 60°C for 24 h, cooled, washed with ethyl acetate and dried.

[0046] The synthesized ionic liquid intermediate was dissolved in water, 1.05 equivalents of lithium bis(trifluoromethanesulfonyl)imide were added, stirred at room temperature for 2 h, then heated to 60°C and stirred for 4 h. After the reaction, the mixture was washed with deionized water and dried to obtain 1-ethyl-3-methylimidazole bis(trifluoromethanesulfonyl)imide ionic liquid.

[0047] (3) The polyglycolic acid prepolymer prepared above and 1-ethyl-3-methylimidazole bis(trifluoromethanesulfonyl)imide ionic liquid were added into a dry reactor in a mass ratio of 1:2, and then La2O3 with a mass% of the polyglycolic acid prepolymer was added into the reactor, and the reaction was carried out at 150°C for 1 hour, and then the temperature was increased by 10°C every 1 hour until the temperature reached 220°C. After maintaining this temperature for 6 hours, the reaction was stopped to obtain a polyglycolic acid with an intrinsic viscosity of 1.33 dL / g.

[0048] Embodiment 2:

[0049] (1) Methyl glycolate is placed in a reactor, and SnCl2 with a mass% of methyl glycolate is added. The mixture is first heated to 100°C at normal pressure and stirred for 1 hour, and then the temperature is increased by 10°C every hour until the temperature reaches 150°C and maintained at this temperature for 3 hours. The reaction is then continued for 3 hours under a vacuum of about 5 kPa to obtain a polyglycolic acid prepolymer.

[0050] (2) Preparation of 1-propyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide ionic liquid:

[0051] N-methylimidazole, bromopropane and toluene were added into a dry reactor in the ratio of 1 mol:1 mol:100 mL, heated and stirred at 60°C for 24 h, cooled, washed with ethyl acetate and dried.

[0052] The synthesized ionic liquid intermediate was dissolved in water, 1.05 equivalents of lithium bis(trifluoromethanesulfonyl)imide were added, stirred at room temperature for 2 h, then heated to 60°C and stirred for 4 h. After the reaction, the mixture was washed with deionized water and dried to obtain 1-propyl-3-methylimidazole bis(trifluoromethanesulfonyl)imide ionic liquid.

[0053] (3) The polyglycolic acid prepolymer prepared above and 1-propyl-3-methylimidazole bis(trifluoromethanesulfonyl)imide ionic liquid were added into a dry reactor in a mass ratio of 1:2, and then La2O3 with a mass% of the polyglycolic acid prepolymer was added into the reactor, and the reaction was carried out at 150°C for 1 hour, and then the temperature was increased by 10°C every 1 hour until the temperature reached 220°C. After maintaining this temperature for 6 hours, the reaction was stopped to obtain polyglycolic acid with an intrinsic viscosity of 1.15 dL / g.

[0054] Embodiment 3:

[0055] (1) Methyl glycolate is placed in a reactor, and SnCl2 with a mass% of methyl glycolate is added. The mixture is first heated to 100°C at normal pressure and stirred for 1 hour, and then the temperature is increased by 10°C every hour until the temperature reaches 150°C and maintained at this temperature for 3 hours. The reaction is then continued for 3 hours under a vacuum of about 5 kPa to obtain a polyglycolic acid prepolymer.

[0056] (2) Preparation of 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide ionic liquid:

[0057] N-methylimidazole, butyl bromide and toluene were added into a dry reactor in the ratio of 1 mol:1 mol:100 mL, heated and stirred at 60°C for 24 h, cooled, washed with ethyl acetate and dried.

[0058] The synthesized ionic liquid intermediate was dissolved in water, 1.05 equivalents of lithium bis(trifluoromethanesulfonyl)imide were added, stirred at room temperature for 2 h, then heated to 60°C and stirred for 4 h. After the reaction, the mixture was washed with deionized water and dried to obtain 1-butyl-3-methylimidazole bis(trifluoromethanesulfonyl)imide ionic liquid.

[0059] (3) The polyglycolic acid prepolymer prepared above and 1-butyl-3-methylimidazole bis(trifluoromethanesulfonyl)imide ionic liquid were added into a dry reactor in a mass ratio of 1:2, and then La2O3 with a mass% of the polyglycolic acid prepolymer was added into the reactor, and the reaction was carried out at 150°C for 1 hour, and then the temperature was increased by 10°C every 1 hour until the temperature reached 220°C. After maintaining this temperature for 6 hours, the reaction was stopped to obtain polyglycolic acid with an intrinsic viscosity of 1.09 dl / g.

[0060] Embodiment 4:

[0061] (1) Methyl glycolate is placed in a reactor, and SnCl2 with a mass% of methyl glycolate is added. The mixture is first heated to 100°C at normal pressure and stirred for 1 hour, and then the temperature is increased by 10°C every hour until the temperature reaches 150°C and maintained at this temperature for 3 hours. The reaction is then continued for 3 hours under a vacuum of about 5 kPa to obtain a polyglycolic acid prepolymer.

[0062] (2) Preparation of 1-benzyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide ionic liquid:

[0063] N-methylimidazole, benzyl bromide and toluene were added into a dry reactor in the ratio of 1 mol:1 mol:100 mL, heated and stirred at 60°C for 24 h, cooled, washed with ethyl acetate and dried.

[0064] The synthesized ionic liquid intermediate was dissolved in water, 1.05 equivalents of lithium bis(trifluoromethanesulfonyl)imide were added, stirred at room temperature for 2 h, then heated to 60°C and stirred for 4 h. After the reaction, the mixture was washed with deionized water and dried to obtain 1-benzyl-3-methylimidazole bis(trifluoromethanesulfonyl)imide ionic liquid.

[0065] (3) The polyglycolic acid prepolymer prepared above and 1-benzyl-3-methylimidazole bistrifluoromethanesulfonyl imide ionic liquid were added to a dry reactor in a mass ratio of 1:2, and then La2O3 with a mass% of the polyglycolic acid prepolymer was added to the reactor, and the reaction was carried out at 150°C for 1 hour, and then the temperature was increased by 10°C every 1 hour until the temperature reached 220°C. After maintaining this temperature for 6 hours, the reaction was stopped to obtain a polyglycolic acid with an intrinsic viscosity of 1.27 dL / g.

Claims

1. A method for preparing polyglycolic acid having high intrinsic viscosity in an ionic liquid, characterized in that: The following steps are involved: The polyglycolic acid prepolymer, the ionic liquid and the polycondensation catalyst are subjected to polycondensation reaction to obtain polyglycolic acid with high intrinsic viscosity.

2. The preparation method according to claim 1, characterized in that: The mass ratio of the polyglycolic acid prepolymer to the ionic liquid is 1:1-2.

3. The preparation method according to claim 1, characterized in that: The polycondensation catalyst is selected from one or more of lanthanum oxide, antimony trioxide, tin oxide, cerium oxide, antimony acetate and zinc acetate.

4. The preparation method according to claim 1, characterized in that: The added amount of the polycondensation catalyst is 0.1-1wt% of the total amount of the reactants (polyglycolic acid prepolymer and ionic liquid).

5. The preparation method according to any one of claims 1 to 4, characterized in that: The preparation method of the polyglycolic acid prepolymer comprises the following steps: Methyl glycolate undergoes an ester exchange reaction under the catalytic action of an ester exchange catalyst to obtain a polyglycolic acid prepolymer.

6. The preparation method according to claim 5, characterized in that: The transesterification catalyst is selected from NaOH, Na2CO3, K2CO3, AlCl3, ZnCl2, SnCl2, H3PW 12 O 40 One or more of.

7. The preparation method according to claim 5, characterized in that: The added amount of the transesterification catalyst is 1% of the mass of methyl glycolate.

8. The preparation method according to any one of claims 1 to 4, characterized in that: The preparation method of the ionic liquid comprises the following steps: A) adding N-methylimidazole and 1-halogenated alkane to toluene to undergo quaternization reaction to obtain the corresponding imidazole-type halogen salt; B) dissolving the above-mentioned imidazole type halide salt in water, and adding bistrifluoromethanesulfonyl imide lithium to carry out ion exchange reaction to obtain an imidazole type ionic liquid with bistrifluoromethanesulfonyl imide as anion.

9. The preparation method according to claim 8, characterized in that: The dosage ratio of the N-methylimidazole, 1-halogenated alkane and toluene is 1 mol: 1 mol: 100 mL.

10. The preparation method according to claim 8, characterized in that: The molar ratio of the imidazole type halide salt to lithium bis(trifluoromethanesulfonyl)imide is 1:1.05.

Citation Information

Patent Citations

  • Preparation method and system of polyhydroxycarboxylate or polyhydroxycarboxylic acid polymer

    CN111647142A

  • Method for generating polyglycolic acid by catalyzing methyl glycolate polymerization with acidic catalyst

    CN111763308A

  • Method for synthesizing glycolide in one step

    CN112010834A

  • Method for preparing high molecular weight polyglycolic acid from glycolic acid or methyl glycolate

    CN107177032A

  • Preparation method of polyglycolic acid

    CN111087580A